The Role Of The Pediatric Nurse In Discharge Planning; Identifying Gaps In Sri Lanka - Subasinghe, Kalpana Jeewanthi; Pathiranage, A.M. Shyama Deepanie (IJNP (Indonesian Journal of Nursing Practices), 2021)
Background: Pediatric discharge planning is a complex process, and that nurses need lengthy preparations. Role confusion among nurses will disrupt the smooth planning of the discharge. In Sri Lanka, although there is a possibility of reducing health costs through effective discharge planning led by pediatric nurses, it is questionable whether Sri Lankan nurses have clarified their role in this process.Method: This systematic review was conducted to map the different roles of nurses in the pediatric discharge planning process. Electronic databases of PubMed and CINAHL were searched for peer-reviewed journal articles among the pediatric population from 2005-2019, using the keywords such as discharge planning, pediatric nurse, care transitions, transitional care, and Sri Lankan nurse.Results: Articles that resulted in the word combination ‘Discharge planning and pediatric nursing (n=329) were used for screening. Two hundred and forty articles out of the nursing scope and sixty articles that do not describe an apparent nursing involvement in the discharge process were excluded, based on abstract review and full-text review, respectively. Sixteen studies were included in the final review. Few literature was found on the topic among Sri Lankan pediatric population. Four main categories of nurses’ roles were identified with the thematic analysis: discharge educator, discharge collaborator, post-discharge care coordinator, and family counselor. Conclusion: In Sri Lanka, no such defined roles of a nurse have been established yet in the discharge planning of pediatric patients. These roles may help nurses carry out discharge planning effectively, and future studies are needed on this topic in Sri Lanka.